Pengaruh Model Pembelajaran Berbasis Masalah (PBM) terhadap Pencapaian Hasil Belajar Matematika Siswa - Salim Salim; Lambertus Lambertus; La Ode Muhammad Bariudin (Jurnal Pendidikan Matematika RAFA, 2020)
This study aimed to determine the influence of PBM model implementation of students' mathematical learning outcomes. The design of this research is quasi experimentation using the posttest only control group pattern. This study was conducted in SMP in Kendari. This research sample was selected using the purposive sampling technique to determine two treatment groups, namely the VIIA class as an experimental class with a problem-based learning (PBM) model and a VIIB class as a control class with a direct learning model. The results showed that there was significantly the influence of PBM model implementation of students' mathematical learning outcomes characterized by elements: (1) Students ' learning activities are superior to being taught with PBM models over direct learning models, (2) Student mathematics learning outcomes in treatment classes with PBM models have a higher average compared to live learning models, (3) PBM models are better compared to live learning models.